2021
DOI: 10.1002/cnma.202100185
|View full text |Cite
|
Sign up to set email alerts
|

Zr‐MOF Combined with Nanofibers as an Efficient and Flexible Capacitive Sensor for Detecting SO2

Abstract: The fabrication of gas sensors with flexible properties and sensitive performances is of great importance for improving wearable sensing electronics. Herein, we coated a metal-organic framework (UiO-66-NH 2 ) on flexible electrospun polyvinylidenefluoride (PVDF) nanofibers as sensing layer for real-time monitoring of toxic SO 2 at room temperature. The developed capacitive sensor possesses a great bending flexibility, excellent cycling stability, high detection sensitivity, light weight as well as portable abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The β-phase content of PVDF with Zr-based MOF increased by 16%, and the output voltage of PVDF with 5 wt% MOF was found to be the highest when it was used for human arterial pulse detection. In addition, Zr-based MOF can also be used for SO 2 detection, and the results show that it has high sensitivity and excellent flexibility [ 125 ]. Roy et al [ 126 ] incorporated 2D MOF into PVDF, and the structure of MOF is shown in Figure 7 (1).…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…The β-phase content of PVDF with Zr-based MOF increased by 16%, and the output voltage of PVDF with 5 wt% MOF was found to be the highest when it was used for human arterial pulse detection. In addition, Zr-based MOF can also be used for SO 2 detection, and the results show that it has high sensitivity and excellent flexibility [ 125 ]. Roy et al [ 126 ] incorporated 2D MOF into PVDF, and the structure of MOF is shown in Figure 7 (1).…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…Gas molecules can be easily adsorbed and enriched on metal nodes and functional groups in organic ligands, thus improving the sensitivity and reducing the detection limit of gas sensors. 26,122 In addition, MOFs can also be used as molecular sieves due to their adjustable pore structures. The selective separation of the target gas molecule from the interfering gas can be achieved by a properly designed pore structure.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Meanwhile, the LOD was calculated to be 0.65 ppm, which is significantly lower than the Occupational Safety and Health Administration (OSHA) warning value for SO 2 gas [116]. Very recently, Zhang et al [28] developed a capacitive-based sensing material using a relatively simple fabrication process (Figure 7a) for the real-time monitoring of SO 2 gas molecules at room temperature. The sensing technology was introduced by using polyvinylidenefluoride (PVDF) nanofibers (with a diameter of 300-400 nm) coated with a thin layer of UiO-66-NH 2 MOF (200 nm in size) (Figure 7b, inset) as a dielectric layer and carbon nanotubes (CNTs) as an electrode.…”
Section: Sulphur Dioxide (So 2 )mentioning
confidence: 99%
“…[27,32]. Capacitive-based sensors are an attractive class of sensors, in which capacitance changes due to the change in the dielectric permittivity upon adsorbing the gas/vapour molecules are detected [28][29][30]. In chemoresistive detectors, electrical conductivity changes as a result of a reaction between the target gas and oxygen molecules adsorbed on the surface of the sensing material [4,21,33].…”
Section: Introductionmentioning
confidence: 99%